Mucosal immune and stress responses of Neoparamoeba perurans-infected Atlantic salmon (Salmo salar) treated with peracetic acid shed light on the host-parasite-oxidant interactions - Lazado, Carlo C.; Strand, David A.; Breiland, Mette W.; Furtado, Francisco; Timmerhaus, Gerrit; Gjessing, Mona C.; Hytterød, Sigurd; Merkin, Grigory V.; Pedersen, Lars-Flemming; Pittman, Karin A.; Krasnov, Aleksei (Frontiers in Immunology, 2022)
Treatment development for parasitic infestation is often limited to disease resolution as an endpoint response, and physiological and immunological consequences are not thoroughly considered. Here we report the impact of exposing Atlantic salmon affected with amoebic gill disease (AGD) to peracetic acid (PAA), an oxidative chemotherapeutic. AGD-affected fish were treated with PAA either by exposing them to 5 ppm for 30 mins or 10 ppm for 15 mins. Unexposed fish from both infected and uninfected groups were also included. Samples for molecular, biochemical and histological evaluations were collected at 24 h, 2 weeks and 4 weeks post treatment. Behavioural changes were observed during PAA exposure and post-treatment mortality was higher in the infected and PAA treated groups, especially in 10ppm-15mins. Plasma indicators showed that liver health was affected by AGD, though PAA treatment did not exacerbate the infection-related changes. Transcriptome profiling in the gills showed significant changes triggered by AGD and PAA treatments, and the effects of PAA were more notable 24 h after treatment. Genes related to immune pathways of B- and T- cells and protein synthesis and metabolism were downregulated, where the magnitude was more remarkable in 10ppm-15mins group. Even though treatment did not fully resolve the pathologies associated with AGD, 5ppm-30mins group showed lower parasite load at 4 weeks post-treatment. Mucous cell parameters (i.e., size and density) increased within 24 h post-treatment and were significantly higher at termination, especially in AGD-affected fish, with some treatment effects influenced by the dose of PAA. Infection and treatments resulted in oxidative stress – in the early phase in the gill mucosa, while systemic reactive oxygen species (ROS) dysregulation was evident at the later stage. Infected fish responded to elevated circulating ROS by increasing antioxidant production. Exposing the fish to a crowding stress revealed interference in the post-stress responses. Lower cortisol response was displayed by AGD-affected groups. Collectively, the study established that PAA, within the evaluated treatment protocols, could not provide a convincing treatment resolution and thus require further optimisation. Nonetheless, PAA treatment altered the mucosal immune and stress responses of AGD-affected Atlantic salmon, shedding light on the host-parasite-treatment interactions.